Livable Eco-Architecture Masdar City, Arabian Sustainable City. (6th January 2016) - Ibrahim, Iman
Abstract: In the age of Global warming, Pollution and running out the Earth of its natural resources, where the future will be governed by the development of clean technologies for sustainable environmental management, highlighting the architects role where it's clear that the building sector is the single largest contributor to increase the phenomena of world climate change. This paper addresses itself to that modified challenge, it attempts to define and clarify eco-Architecture as a framework for a comprehensive understanding, and then it will focus on Masdar city as the first eco city in Arab world.